Household saving in the UK - James Banks; Sarah Tanner (Institute for Fiscal Studies (IFS), 1999)
The gradual shift in responsibility for welfare provision, from the government to individuals, is making household saving and wealth holding a key policy concern. Yet remarkably little is known about how much households save or the forms in which they save.Unlike income or expenditure, there is no official individual or household survey collecting detailed information on saving and wealth holdings on an ongoing basis. This has limited the possible analysis of how saving responds to the incentives created by policy changes.This report reviews the economics of household saving, the taxation of financial assets in the UK and official sources of information on saving and wealth. It also provides new information on trends in asset holding in the household population over the period 1978-96 and a detailed description of asset and wealth holdings in 1997-98.
Keywords: 330